Comparative Outcomes of Kangaroo Mother Care versus Conventional Incubator Care in Moderately Low Birth-Weight Infants (>1500 g): A Randomized Controlled Trial in a Tertiary Pakistani Hospital - Anam Amjad Buttar, Momna Ejaz, Raima Siddiqui, Amber Rehman, Hammal Khan Naseer Baloch, Muhammad Sami Iqbal (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Kangaroo mother care (KMC) has been proposed as an effective alternative toconventional incubator care for low birth-weight infants, but comparative randomized evidence for moderately low birth-weight neonates